Surgical treatment for myelodysplastic clubfoot, - Alexandre Zuccon; Sérgio Inácio Cristiano Cardoso; Fábio Peluzo Abreu; Antonio Carlos Fernandes (Revista Brasileira de Ortopedia, 2014)
Objective:To analyze the results from surgical treatment of 69 cases of clubfoot in 43 patients with myelodysplasia according to clinical and radiographic criteria, at our institution between 1984 and 2004.Methods:This was a retrospective study involving analysis of medical files, radiographs and consultations relating to patients who underwent surgical correction of clubfoot. The surgical technique consisted of radical posteromedial and lateral release with or without associated talectomy.Results:The patients' mean age at the time of the surgery was four years and two months, and the mean length of postoperative follow-up was seven years and two months. Satisfactory results were achieved in 73.9% of the feet and unsatisfactory results in 26.1% (p < 0.0001).Conclusion:Residual deformity in the immediate postoperative period was associated with unsatisfactory results. Opening of the Kite (talocalcaneal) angle in feet that only underwent posteromedial and lateral release, along with appropriate positioning of the calcaneus in cases that underwent talectomy, was the radiographic parameter that correlated with satisfactory results.